2013
DOI: 10.1097/mlr.0b013e31828d4d0c
|View full text |Cite
|
Sign up to set email alerts
|

Is Medical Home Enrollment Associated With Receipt of Guideline-Concordant Follow-up Care Among Low-Income Breast Cancer Survivors?

Abstract: Results suggest that CCNC enrollment is associated with guideline-concordant follow-up care for Medicaid-insured survivors. Given the growing population of cancer survivors and increased emphasis on primary care medical homes, future studies should explore what factors are associated with medical home participation and whether similar findings are observed with extended follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…As we have reported elsewhere [10], breast cancer survivors who were enrolled in CCNC were significantly more likely to receive guideline-concordant follow-up care. By virtue of their patient-centered primary care approach, CCNC and other PCMH programs hold huge potential for reducing costs (by proactively managing treatment-related AEs in a primary care setting) and for reducing preventable inpatient admissions and ED visits.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…As we have reported elsewhere [10], breast cancer survivors who were enrolled in CCNC were significantly more likely to receive guideline-concordant follow-up care. By virtue of their patient-centered primary care approach, CCNC and other PCMH programs hold huge potential for reducing costs (by proactively managing treatment-related AEs in a primary care setting) and for reducing preventable inpatient admissions and ED visits.…”
Section: Discussionsupporting
confidence: 57%
“…Because Medicaid enrollment can be transient [11], we only included patients who had at least 12 months of Medicaid enrollment during the 15-month postdiagnosis period, so that most of their service claims could be captured. These exclusions followed a protocol that we described previously in another paper [10]. We further excluded patients who were eligible to receive both Medicare and Medicaid benefits, because complete treatment claims for these patients were not available.…”
Section: Cohort Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using methods consistent with those described in previously published research [10,31,43], we adjusted for comorbidities identified from Medicare claims using the National Cancer Institute Combined Index, with some modification to allow us to capture comorbid conditions co-occurring during the cancer treatment period [44]. Specifically, comorbidity was measured according to the Charlson Index from 3 months prior to diagnosis through 12 months after diagnosis, and breast-cancer-specific weights were calculated for each condition [44].…”
Section: Methodsmentioning
confidence: 99%